Description of the female of Aysha yacupoi Brescovit 1992 (Araneae: Anyphaenidae) - Argañaraz, Carina Inés (2013)
The female of Aysha yacupoi Brescovit, 1992 is described and illustrated for the first time. Males and female specimens were observed together in the same plants. Some data on natural history are presented.